Co-Reactivation of Cytomegalovirus and Epstein-Barr Virus Was Associated With Poor Prognosis After Allogeneic Stem Cell Transplantation - Zhou, Jing-Rui; Shi, Da-Yu; Wei, Rong; Wang, Yu; Yan, Chen-Hua; Zhang, Xiao-Hui; Xu, Lan-Ping; Liu, Kai-Yan; Huang, Xiao-Jun; Sun, Yu-Qian (Frontiers in Immunology, 2021)
Reactivation of Cytomegalovirus (CMV) or Epstein-Barr virus (EBV) are common after hematopoietic stem cell transplantation (HSCT). Previous researches have demonstrated that either CMV or EBV reactivation is associated with poor outcomes of HSCT. However, few studies investigate the impact of CMV and EBV co-reactivation after HSCT. In this study, we described the clinical characteristics of HSCT recipients with CMV and EBV co-reactivation (defined as CMV and EBV viremia occur at the same period of time). We conducted a longitudinal study of 247 patients who underwent HSCT in our center. A total of 24 (9.7%) patients had CMV and EBV co-reactivation. These patients showed higher incidence of viral pneumonitis (P=0.005). Patients with CMV and EBV co-reactivation had significant lower 1-year overall survival (OS) (P=0.004) and lower 1-year leukemia free survival (LFS) (P=0.016). Our further analysis suggested that duration of CMV (P=0.014), EBV (P＜0.001) and CD4+CD25+ T cell counts at day 30 post-transplantation (P=0.05) are independent risk factors of virus co-reactivation. In conclusion, patients developed co-reactivation of CMV and EBV had poor prognosis in terms of lower 1-year OS and LFS, and the CMV and EBV co-reactivation was associated with prolonged CMV or EBV duration and poor CD4+CD25+ T cell reconstitution at day 30 post-transplantation.